2020
DOI: 10.1111/1467-9604.12317
|View full text |Cite
|
Sign up to set email alerts
|

Building student‐teacher relationships and improving behaviour‐management for classroom teachers

Abstract: Teachers can at times view behavioural intervention procedures as time‐consuming. Thus, socially‐valid classroom‐based interventions are a critical component to behavioural success. This study examined the effects of traditional behavioural interventions with two kindergarten students presenting with challenging behaviours, including aggression, tantrums and noncompliance. Notably, it was found that traditional behavioural procedures were not sufficient to substantially reduce the behaviours alone. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The themes suggest that student-teacher relationships are vital. These results match the recent recommendations of Yassine et al (2020), who suggested that improving student-teacher relationships is a key component in the success of in-class interventions for disruptive behaviour. Our results are also supported by two longitudinal studies conducted by Hamre and Pianta (2001) and Hughes (2011), who investigated the overall influence of student-teacher relationship quality on student social and academic outcomes.…”
Section: Experience With and Knowledge Of Interventionssupporting
confidence: 89%
“…The themes suggest that student-teacher relationships are vital. These results match the recent recommendations of Yassine et al (2020), who suggested that improving student-teacher relationships is a key component in the success of in-class interventions for disruptive behaviour. Our results are also supported by two longitudinal studies conducted by Hamre and Pianta (2001) and Hughes (2011), who investigated the overall influence of student-teacher relationship quality on student social and academic outcomes.…”
Section: Experience With and Knowledge Of Interventionssupporting
confidence: 89%
“…By instilling quality teacher–student relationships, there is a correlation between students’ academic success and behavioral outcomes (Li, 2015). Behavior outcomes were also the focus of work by Yassine and colleagues (2020), indicating that focusing on the teacher–student relationship, including the components that build relationships, impacts student behavior and is a key piece of academic success.…”
Section: Resultsmentioning
confidence: 99%
“…In their longitudinal study focussing on associations of student-teacher relationships and behavioural and emotional strengths on academic achievement in a group of Grade 5-7 Finnish studentsSointu et al (2017) reported that a positive student-teacher relationship correlated with higher academic achievement. In addition,Yassine et al (2020) found a significant reduction in challenging and harmful behaviours in Kindergarten students due to the introduction of a relationship building component to a behaviour management plan. The importance of strong student-teacher…”
mentioning
confidence: 99%